2020
DOI: 10.1007/s11695-020-04830-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Bariatric Surgery: Results from a Worldwide Survey

Abstract: Background The ongoing "coronavirus disease 19" (COVID-19) pandemic has had a strong effect on the delivery of surgical care worldwide. Elective surgeries have been canceled or delayed in order to reallocate resources to the treatment of COVID-19 patients. Currently, the impact of the COVID-19 pandemic on bariatric and metabolic surgical practice remains unclear. Methods An internet-based online survey was performed among bariatric surgeons worldwide. The survey was sent to bariatric surgeons via the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
1
16
0
2
Order By: Relevance
“…Traditional consultations consisted of 15–20-min face-to-face consultations with a prior blood test and face-to-face anthropometry of the patient; however, telephone visits involve questionnaires like the one used, without blood tests and with anthropometric data self-reported by the patients. Bariatric surgery has been inevitably affected by the COVID-19 pandemic, as indicated by Lazaridis et al [ 11 ] in a worldwide survey. In our study, we have detected how a 49.3% of patients did not attend their visit in the Nutrition Unit and this was related to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional consultations consisted of 15–20-min face-to-face consultations with a prior blood test and face-to-face anthropometry of the patient; however, telephone visits involve questionnaires like the one used, without blood tests and with anthropometric data self-reported by the patients. Bariatric surgery has been inevitably affected by the COVID-19 pandemic, as indicated by Lazaridis et al [ 11 ] in a worldwide survey. In our study, we have detected how a 49.3% of patients did not attend their visit in the Nutrition Unit and this was related to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients have struggled for many years with noninvasive measures like diet, exercise, and pharmacotherapy before surgery. The current COVID-19 pandemic, with its high morbidity and mortality, has led to the cancellation of millions of surgeries, including all bariatric surgery procedures [ 10 , 11 ]. Many centers were afraid to resume activity due to the risk of contamination for patients with morbid obesity or additional deterioration of their pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of face-to-face clinical care has also impacted on the care of chronic diseases such as hypertension and diabetes, which will likely have associated long-term costs, especially in obese patients. A world-wide survey among bariatric surgeons found that 84.6% of surgeons had postponed primary or redo bariatric procedures in light of the COVID-19 pandemic 28 . A J o u r n a l P r e -p r o o f similar survey in the UK found that 97% of bariatric surgeons ceased their outpatient clinics for both new and follow-up patients and almost 60% of bariatric surgeons stopped placing new patients on their waiting lists 29 .…”
Section: Healthcare and The Covid-19 Impact On Obesitymentioning
confidence: 99%